43.1k views
3 votes
When rewriting in the form y=a(x-h)+k, by completing the square, the relation y=-x*2+6x+12 becomes:

2 Answers

1 vote

Answer:

Explanation:

you can complete the square or use a calculator online that does it for you.

the equation is in the for y = a(x-h)^2 + k

it should be y = (x + 3)^2 + 3

User Karl Der Kaefer
by
5.1k points
1 vote

Answer:

The correct answer is
y = - (x - 3)^(2) +21.

Explanation:

To solve this equation (y =
-x^(2) +6x + 12), we want to first complete the square. To do this, we want to add a -9 to the expression in order to achieve
y = -x^(2) +6x - 9 + 12.

Then, you want to add the -9 to the other side of the equation to get
y - 9 = -x^(2) + 6x - 9 + 12.

Then, we factor out the negative sign from the right side of the equation. This is a negative 1 that can therefore make the polynomial easier to factor. This leaves us with
y - 9 = -(x^(2) -6x+9) + 12.

Now, we use an identity in algebra that is difference of two squares identity. This says that
a^(2) -2ab +b^(2) =(a-b)^(2).

So, we will then factor the trinomial -
x^(2) -6x+9 to get
-(x-3)^(2). Our new and updated equation is
y-9 = -(x-3)^(2) +12.

Now, we move the constant of -9 to the right side of the equation. This just means we are going to add this to 12. This gives us
y = -(x-3)^(2) +21.

This is our final equation.

User Yevhen Kuzmovych
by
4.7k points